Should undergraduate medical students be regulated? Yes. (5th May 2010) - Dacre, Jane; Raven, Peter
Abstract : Jane Dacre and Peter Raven are convinced that regulation will prevent potentially dangerous medical students from becoming dangerous doctors, but Edward Davies (doi:10.1136/bmj.c1806 ) thinks it an absurd over-reaction